UTILIZATION OF GENERAL ELECTRONIC DATABASES BY UNDERGRADUATE STUDENTS OF BESTLINK COLLEGE OF THE PHILIPPINES (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
General electronic databases are accessible through the internet and library systems, providing relevant and useful information based on individual research needs. Examples of these databases include Philippine e-Journals, ProQuest, ScienceDirect, ERIC, SCOPUS, and JSTOR. These platforms contain reliable and updated resources that support research development and enhance access to related studies in various fields. This study employed a quantitative research approach using a stratified random sampling technique to gather data. The study involved 350 bona fide undergraduate students from seven different courses at Bestlink College of the Philippines as respondents. The findings revealed that most library users are female, aged 20–21 years old, with second-year undergraduate students making up the largest group. Among the courses, Bachelor of Science in Criminology (BSCrim) had the highest frequency of users. In terms of usability, respondents found general electronic databases useful for obtaining information. Regarding awareness, most students were aware of the existence of these databases. Finally, in terms of relevance, respondents agreed that these databases provide valuable resources for retrieving related information. The study recommends that the institution maximize the use of library resources to enhance research development. Additionally, the library should actively promote its electronic databases, including the student learning management system’s "Libraries" icon, to encourage wider utilization among students.
Keywords: electronic resources; general databases; usability; awareness; relevance